2007 IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications 2007
DOI: 10.1109/pimrc.2007.4394110
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Integrated LBS-Enabled, Mobile Auctions Marketplace for Logistics Services

Abstract: Rapid mobile communications penetration in Europe set the basis for the evolution of innovative mobile commerce applications. The integration of mobile commerce and Location-Based Services provides the infrastructure for geographically-focused trade of logistics services, such as the freight transport.The present paper presents a pragmatic information flow model of an auction-based freight transport marketplace, where potential bidders (carriers) are selected based on their current location. To safeguard aucti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Various combinations of heterogeneous communication services like internet, mobile and GPS can be applied to form value-added applications, which are usually called locationbased services (LBS). Emiris et al (2007) demonstrated the coupling of LBS and mCommerce in auction environments to create an m-auction environment for use in logistics-related services. In particular, they examined the case of auctions where several bidders compete to win a freight contract by offering a lower price.…”
Section: Value-added Applicationsmentioning
confidence: 99%
“…Various combinations of heterogeneous communication services like internet, mobile and GPS can be applied to form value-added applications, which are usually called locationbased services (LBS). Emiris et al (2007) demonstrated the coupling of LBS and mCommerce in auction environments to create an m-auction environment for use in logistics-related services. In particular, they examined the case of auctions where several bidders compete to win a freight contract by offering a lower price.…”
Section: Value-added Applicationsmentioning
confidence: 99%
“…Emiris and Marentakis (2010b),Marentakis and Emiris (2010a),Petridis et al, (2010),Marentakis and Emiris (2009),Emiris and Marentakis (2009),Anagnostou et al, (2009),Emiris and Marentakis (2008),Marentakis and Emiris (2008),Emiris et al, (2007a),Marentakis et al, (2007).…”
mentioning
confidence: 99%